HUBUNGAN ADIKSI TELEPON PINTAR TERHADAP REFLEKS BERKEDIP DAN KUANTITAS AIR MATA PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA TAHUN AKADEMIK 2019/2020 - Salma Tania (2020)
Increasing the use of smartphones will increase the risk of addiction which causes a number of health problems, including vision function. This research was conducted to determine the relationship between smartphone addiction with blink reflex and tear quantity in medical students at Universitas Pembangunan Nasional Veteran Jakarta. This study used a cross-sectional design, a total of 88 subjects according to the criteria was determined using a simple random sampling technique. The questionnaire Smartphone Addiction Scale (SAS) was used in the study to measure addiction, the number of blinking reflex in one minute is calculated using video recording, and the tear quantity was measured using the Schirmer I Test. Based on the characteristics of the subjects aged 20 (18-23) years, the majority were female with a duration of smartphone usage ˃ 6 hours and used 21 - 50 times per day for social media activities, subjects were aware of the blue light effect but didn't use the blue light filter on their smartphone. The results showed 52.3% of subjects had a smartphone addiction with the amount of blink reflexes 11 (3-44) times / minute and a quantity of tears 25 (2-35) millimeters in 5 minutes. Mann-Whitney test results showed no relationship between smartphone addiction with blink reflexes p = 0.537 (p˃0.05) and there was a relationship between smartphone addiction with tear quantity p = 0.011 (p˂0.05).